Randang Information Media Design As A Minangkabau Culinary Identity - Putri, Salsabila; Rahman, Fadlul; Ananta, Aryoni (Institut Seni Indonesia Padang Panjang, 2024)
Culinary in Indonesia is very diverse, including randang, which comes from West Sumatra. Randang is a typical Minangkabau culinary identity known for its deliciousness. Randang has a complex cultural background. In the context of Minangkabau culture, the presentation of randang has a deep symbolic value and cannot be replaced by other dishes, so the term